Analysis Of The Factors Net Benefits Of Flight Simulation Online System - Pramadya, Rifky; Retnowardhani, Astari; Gea, Diyurman (Universitas Pahlawan Tuanku Tambusai, 2023)
Flight simulation games are one of the many new technologies that have emerged due to the development of digital games and current gamification technologies. Flight simulation games released by several developers are currently still standalone and cannot be connected to each other. An online flight simulation system has been developed to be able to link and connect between flight simulation game developers, so that users can connect with each other and make the simulation more real. The present online flight simulation system can make flight simulator games into more serious games, but it still has a issues, such as people who rarely utilize the system. The purpose of this research is to find out and identify the factors of net benefits using flight simulation online system by using modification of the DeLone and McLean and UTAUT2 models conducting PLS-SEM analysis. Respondents in this study were users who had used the system with a total of 366 respondents. The results of this study show that System Quality, Service Quality, Effort Expectancy and Social Influence do not have a significant impact on System Use, then Information Quality and Perceived Enjoyment have a positive and significant impact on System Use, then Service Quality does not have a significant impact on User Satisfaction, then Information Quality and System Quality has a positive and significant impact on User Satisfaction, then System Use and User Satisfaction have a positive and significant impact on Net Benefits.